Diseño de indumentaria de protección personal agrícola para la empresa Agrolabsa de la parroquia Santa Rosa de la ciudad de Ambato - Calvopiña Sánchez, Mónica del Rocío (2025)
Personal protective clothing not only provides protection for workers but also enhances their productivity, well-being, and safety, with the aim of promoting a safe and efficient work environment. Therefore, designing personal protective clothing is much more than delivering a finished product; it requires an in-depth analysis of user needs to ensure precise decision-making that meets both the aesthetic and functional requirements of clients. Occupational safety in the agricultural sector, particularly in the context of personal protective clothing, is of paramount importance, especially when handling agrochemical products. This thesis focuses on designing work coveralls specifically for employees of Agrolabsa, a company located in Ambato, whose workers face high-risk conditions during the manual mixing of solid agrochemical products using shovels. The initiative aims to ensure maximum protection against occupational hazards by minimizing exposure to agrochemicals and reducing workplace accidents. This approach not only enhances the company’s operational efficiency but also positions Agrolabsa as a responsible organization that complies with standardization and personal protection regulations, avoiding potential fines or penalties during future inspections. The optimal garment chosen was the work coverall due to its silhouette and functionality, combining standardized regulations with high-quality technical textiles. These textiles offer superior resistance, durability, comfort, and breathability, while incorporating essential features such as reinforced and sealed seams, precise adjustments, and additional reinforcements. Interviews with the manager, workers, and textile engineers, as well as an analysis of relevant standards, were invaluable in identifying the risks and needs of the workforce